ANALYSIS OF THE QUALITY OF FLOUR FROM DIFFERENT SYSTEMS OF THE TECHNOLOGICAL PROCESS OF A FLOUR MILL - D. ZHYGYNOV; V. KOVALOVA; A. DRAGOMYR; H. ZHYHUNOVA; К. ZHANABAYEVA (Zernovì Produkti ì Kombìkorma, 2019)
Research in the article is aimed to determining the quality of flour from different systems of the technological process of a wheat milling. Samples of flour were obtained at the mill "Rivne Boroshno". Private enterprise "Rivne Boroshno" is one of the largest producers of wheat flour in the western region with a capacity of 180 tons /day. Flour obtained from various systems of milling process, has a very large variety of quality indicators. Whiteness, Gluten Deformation Index, Gluten Content, Protein Content, Ash Content, Water Absorbing Capacity, FN, SD, the rheological properties of dough on the Mixolab device, as well as the quality of baked bread have been evaluated. During the study, the variability of flour quality indicators on various systems was found. Whiteness varied – from 1 to 71 units, Gluten Deformation Index – from 40 to 100 units, Gluten Content – from 2 to 36 %, Protein Content – from 9,8 to 18,2 %, the FN – from 275 to 374 s, SD – from 15 to 30,3 UCD, Ash Content – from 0,31 to 2,23 %, Water Absorbing Capacity – from 53,5 to 69,7 %. In the process of grinding grain and intermediate products, more than twenty flour streams of different quality are produced at the flour mill. From these streams it is required to receive only one or several grades of flour. Naturally, if only one variety is produced, then all flows from different systems are sent to it. The weighted average quality indicators of flour should comply with the requirements of the standard for this grade in terms of Ash Content, Gluten Content, etc. The maximum Ash Content is observed in the streams from the last reduction systems, as well as from break systems in the milling process, where products with a large number of brans are milled. At the same time, the flour from the central parts of the endosperm is slightly less gluten, but more starch than in the flour from the peripheral parts of the endosperm, which are grinding on subsequent reduction systems. For the research, samples of flour were taken from each system of the technological process. For convenience, we have arranged them for quality using the indicator of whiteness. One of the main indicators of the quality of flour, which determines its grade, is whiteness. In the studied samples, the values of the whiteness index range from 71 to 1 unit.